Halide solid electrolyte and preparation method and application thereof

By using a core-shell structure, using LiaMXb as the core and nLiX-GaF3 as the shell, the shell is formed by ball milling reaction, which solves the problem that halide solid electrolytes in the prior art is difficult to have high oxidation stability and flexibility, and achieves efficient battery circulation and rate performance.

CN119518077APending Publication Date: 2025-02-25ZHEJIANG INTELLIGENT TRANSPORTATION TECHNOLOGY INNOVATION CENTER +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411731021.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing halide solid electrolytes are difficult to have both oxidation stability of 4.2V or above and have good texture flexibility, resulting in poor performance of the capacity and rate performance of the positive electrode active material, affecting the cycle performance and rate performance of the battery.

Method used

The halide solid electrolyte with a core-shell structure is LiaMXb, and the chemical formula of the shell material is nLiX-GaF3. The shell layer is formed under anhydrous conditions through ball milling reaction, the lithium ion parameters a and halide ion parameters b are adjusted, and the thickness of the shell layer and the molar ratio of LiX and GaF3 are controlled to improve the softness and chemical stability of the electrolyte.

Benefits of technology

The overall chemical structure stability, high ionic conductivity and high electrochemical oxidation stability of the halide solid electrolyte are achieved, while improving the flexibility of the electrolyte surface, enhancing the capacity and rate performance of the positive electrode material, and improving the cycle performance and rate performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119518077A_ABST
    Figure CN119518077A_ABST
Patent Text Reader

Abstract

The invention relates to a halide solid electrolyte and a preparation method and application thereof. Wherein the halide solid electrolyte comprises an inner core and a shell layer coating the surface of the inner core, the chemical general formula of an inner core material is LiaMXb, the chemical general formula of a shell layer main body material is nLiX-GaF3, and a is greater than or equal to 2 and less than or equal to 4lt; b is smaller than or equal to 7, n is larger than or equal to 1 and smaller than or equal to 5, M is selected from at least one of In, Zr, Hf or lanthanide, and X is selected from at least one of Cl, Br or I. The halide solid electrolyte can maintain the stable overall chemical structure, high ionic conductivity and high electrochemical oxidation stability, and the surface of the halide solid electrolyte has good flexibility, so that the prepared battery has excellent cycle performance and rate capability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and particularly to a halide solid electrolyte, a preparation method thereof, and an application thereof. Background Art

[0002] Halide solid electrolytes have attracted much attention due to their many advantages such as high ionic conductivity and high safety. However, existing halide solid electrolytes are difficult to simultaneously have oxidation stability above 4.2V and good texture softness, resulting in poor capacity and rate performance of the positive electrode active material, and further affecting the cycle performance and rate performance of the battery. Summary of the Invention

[0003] Based on this, it is necessary to provide a halide solid electrolyte, a preparation method thereof, and an application thereof for the above problems. The halide solid electrolyte can maintain the stability of the overall chemical structure, high ionic conductivity, and high electrochemical oxidation stability, while having good softness on its surface, so that the prepared battery has excellent cycle performance and rate performance.

[0004] A halide solid electrolyte, the halide solid electrolyte includes a core and a shell layer coated on the surface of the core, and the chemical general formula of the core material is Li a MX b , and the chemical general formula of the main material of the shell layer is nLiX-GaF3, where 2≤a≤4, 4<b≤7, 1≤n≤5, M is selected from at least one of In, Zr, Hf, or a lanthanide element, and X is selected from at least one of Cl, Br, or I.

[0005] In one embodiment, 2.5≤a≤3.5, 5≤b≤6.5, 1.5≤n≤4;

[0006] And / or, M is selected from at least one of In, Zr, Hf, Y, Sc, Dy, Ho, Er, or Yb;

[0007] And / or, X is selected from Cl and / or Br.

[0008] In one embodiment, the thickness of the shell layer is 1nm-50nm.

[0009] In one embodiment, the median particle size of the halide solid electrolyte is 0.05μm-100μm.

[0010] The halide solid electrolyte of the present invention has a core-shell structure, wherein the core material only contains Li a MX b , by using Li a MX bThe characteristics effectively ensure the overall chemical structure stability, high ionic conductivity, and high electrochemical oxidation stability of the halide solid electrolyte. At the same time, the surface shell material is basically only nLiX-GaF3. Utilizing the soft texture characteristic of nLiX-GaF3, the mechanical properties of the surface of the halide solid electrolyte can be significantly improved, making the surface of the halide solid electrolyte have good softness, enabling it to form a denser physical contact with the cathode active material, reducing the interfacial impedance, and thus enabling the cathode material to have higher capacity and rate performance. Therefore, the halide solid electrolyte of the present invention can have good softness on its surface while maintaining the overall chemical structure stability, high ionic conductivity, and high electrochemical oxidation stability, making the prepared battery have both excellent cycle performance and rate performance.

[0011] A preparation method of a halide solid electrolyte as described above, comprising the following steps:

[0012] Provide Li a MX b material, wherein 2 ≤ a ≤ 4, 4 < b ≤ 7, M is selected from at least one of In, Zr, Hf or lanthanide elements, and X is selected from at least one of Cl, Br or I;

[0013] Perform ball milling reaction on the Li a MX b material and GaF3 under anhydrous conditions, so that a shell layer is formed on the surface of the Li a MX b material to obtain a halide solid electrolyte, wherein the mass ratio of the Li a MX b material to the GaF3 is 1:0.003 - 1:0.02, the ball milling speed is 500 rpm - 800 rpm, and the ball milling time is 1 min - 10 min.

[0014] In one embodiment, in the step of performing ball milling reaction on the Li a MX b material and the GaF3 under anhydrous conditions, at least one of the following conditions is satisfied:

[0015] (1) The ball milling medium is selected from at least one of zirconia and silicon nitride, and the ball-to-material ratio is 10:1 - 50:1;

[0016] (2) Perform ball milling reaction on the Li a MX b material and the GaF3 under vacuum or dry inert atmosphere.

[0017] In one embodiment, the Li a MX bThe preparation method of the material comprises the following steps: taking Li a MX b , where 2≤a≤4 and 4<b≤7 as a reference, ball-milling the halide of Li and the halide of M, and then sintering to obtain the Li a MX b material.

[0018] In one embodiment, in the preparation method of the Li a MX b material, at least one of the following conditions is satisfied:

[0019] (1) The ball-milling speed is 400 rpm - 800 rpm, and the ball-milling time is 5 h - 30 h;

[0020] (2) The sintering process is carried out in a nitrogen atmosphere and / or an inert atmosphere, where the inert atmosphere is selected from an argon atmosphere and / or a helium atmosphere;

[0021] (3) The sintering temperature is 100°C - 320°C, and the sintering time is 1 h - 40 h.

[0022] In the preparation method of the halide solid electrolyte of the present invention, by using the ball-milling method, and defining the ball-milling conditions and the mass ratio of the Li a MX b material and GaF3, an in-situ reaction occurs between GaF3 and the halide of Li on the surface of the Li a MX b material to generate nLiX-GaF3, thereby forming a shell layer uniformly coated on the surface of the Li a MX b material, and the shell layer material is basically only nLiX-GaF3, and the reaction conditions are relatively mild and the operation method is simple. Therefore, the preparation method of the halide solid electrolyte of the present invention has a simple operation method, low cost, is easy to prepare in large quantities, and is suitable for industrial production.

[0023] A secondary battery, the secondary battery includes the halide solid electrolyte as described above.

[0024] A vehicle, the vehicle includes the secondary battery as described above. Description of the Drawings

[0025] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following will briefly introduce the drawings required for use in the description of the embodiments or the prior art. Obviously, the drawings in the following description are only some embodiments recorded in the present invention. For those of ordinary skill in the art, other drawings can be obtained based on these drawings without creative efforts.

[0026] Figure 1 Electron micrograph of the halide solid electrolyte prepared in Example 1 of the present invention. Detailed implementation mode

[0027] For ease of understanding the present invention, the present invention will be described in more detail below. However, it should be understood that the present invention can be implemented in many different forms and is not limited to the embodiments or examples described herein. On the contrary, these embodiments or examples are provided to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0028] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the technical field to which the present invention belongs. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments or examples and are not intended to limit the present invention. The optional scope of the term "and / or" used herein includes any one of two or more related listed items, and also includes any and all combinations of the related listed items. The any and all combinations include any two related listed items, any more related listed items, or the combination of all related listed items.

[0029] The halide solid electrolyte provided by the present invention, the halide solid electrolyte includes a core and a shell layer coated on the surface of the core, and the chemical general formula of the core material is Li a MX b , and the chemical general formula of the main material of the shell layer is nLiX-GaF3, where 2≤a≤4, 4<b≤7, 1≤n≤5, M is selected from at least one of In, Zr, Hf or lanthanide elements, and X is selected from at least one of Cl, Br or I. It can be understood that the molecular general formula of the halide solid electrolyte of the present invention is Li a MX b @nLiX-GaF3.

[0030] The halide solid electrolyte of the present invention has a core-shell structure, wherein the core material contains only Li a MX b , using Li a MX bThe characteristics of the solid electrolyte effectively ensure the overall chemical structure stability, high ionic conductivity and high electrochemical oxidation stability of the halide solid electrolyte. At the same time, the surface shell material is basically only nLiX-GaF3. The soft texture of nLiX-GaF3 itself can significantly improve the mechanical properties of the surface of the halide solid electrolyte, so that the surface of the halide solid electrolyte has good flexibility, and can form a denser physical contact with the positive electrode active material, further reducing the interface impedance, so that the positive electrode material has a higher capacity and rate performance. Therefore, the halide solid electrolyte of the present invention can have good flexibility on its surface while maintaining the overall chemical structure stability and high electrochemical oxidation stability, so that the prepared battery has both excellent cycle performance and rate performance.

[0031] In the present invention, the core material of the halide solid electrolyte has the general chemical formula Li a MX b , the lithium ion parameter a and / or the halogen ion parameter b can be adjusted according to actual needs to obtain a core with a different molecular formula. Furthermore, 2.5≤a≤3.5, 5≤b≤6.5. Such a setting is conducive to further improving the chemical structure stability and high electrochemical oxidation stability of the halide solid electrolyte. It can be understood that according to the chemical formula nLiX-GaF3 of the shell main material, the molar ratio of LiX and GaF3 is n:1, and further, 1.5≤n≤4. By regulating the molar ratio of LiX and GaF3, it is beneficial to further improve the softness of the surface of the halide solid electrolyte.

[0032] It should be noted that the chemical formula of the core material in the present invention is Li a MX b , the ionic conductivity of the inner core can be greater than or equal to 1mS / cm, the electrochemical oxidation stability potential is greater than or equal to 4.3V, and the Young's modulus is 20GPa-40GPa, preferably 25GPa. At the same time, by utilizing the soft texture of nLiX-GaF3 itself, the Young's modulus of the shell can be less than 10GPa. Therefore, the ionic conductivity of the halide solid electrolyte of the present invention is above 0.8mS / cm, the electrochemical oxidation stability potential is above 4.2V, and the Young's modulus of its surface is below 12GPa.

[0033] In one embodiment, the lanthanide element is selected from at least one of Y, Sc, Tb, Dy, Ho, Er, Tm, Yb or Lu, and further, the lanthanide element is selected from at least one of Y, Sc, Dy, Ho, Er or Yb. It is understood that, preferably, the M is selected from at least one of In, Zr, Hf, Y, Sc, Dy, Ho, Er or Yb.

[0034] In one embodiment, X is selected from Cl and / or Br, preferably Cl.

[0035] Optionally, the thickness of the shell layer is 1 nm - 50 nm. It can be understood that the thickness of the shell layer in the present invention can be any value selected from 1 nm - 50 nm. Specifically, the thickness of the shell layer includes but is not limited to 1 nm, 5 nm, 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm. By setting it like this, the softness of the surface of the halide solid electrolyte can be controlled by adjusting the thickness of the shell layer, and while better maintaining the overall chemical structure stability, high ionic conductivity and high electrochemical oxidation stability of the halide solid electrolyte, the softness of the surface of the halide solid electrolyte can be further improved.

[0036] Optionally, the median particle size of the halide solid electrolyte is 0.05 μm - 100 μm. It can be understood that the median particle size of the halide solid electrolyte in the present invention can be any value selected from 0.05 μm - 100 μm. Specifically, the median particle size of the halide solid electrolyte includes but is not limited to 0.05 μm, 0.1 μm, 0.2 μm, 2 μm, 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm, 100 μm, preferably 0.2 μm - 20 μm. By setting it like this, it is beneficial to further improve the lithium ion conductivity of the halide solid electrolyte, and at the same time, the halide solid electrolyte can be better dispersed in the positive electrode active material.

[0037] It should be noted that the present invention does not particularly limit the morphology of the halide solid electrolyte, which can be spherical or other shapes, such as elliptical.

[0038] Meanwhile, the present invention also provides a preparation method of a halide solid electrolyte, including the following steps:

[0039] S1, providing Li a MX b material, wherein 2 ≤ a ≤ 4, 4 < b ≤ 7, M is selected from at least one of In, Zr, Hf or lanthanide elements, and X is selected from at least one of Cl, Br or I.

[0040] Specifically, in step S1, the preparation method of the Li a MX b material includes the following steps: Based on Li a MX b , 2 ≤ a ≤ 4, 4 < b ≤ 7, the halide of Li and the halide of M are subjected to ball milling treatment, and then sintered to obtain the Li a MXb Material.

[0041] Optionally, the ball milling speed is 400rpm-800rpm. It can be understood that the ball milling speed includes but is not limited to 400rpm, 500rpm, 600rpm, 700rpm, and 800rpm.

[0042] Furthermore, the ball milling time is 5h-30h; it can be understood that the ball milling time includes but is not limited to 5h, 10h, 20h, and 30h.

[0043] In the present invention, the ball milling speed and the ball milling time can be adjusted to make the ball milling mixing of the Li halide and the M halide more uniform.

[0044] In one embodiment, the Li halide and the M halide are ball-milled using a planetary ball mill.

[0045] Optionally, the sintering temperature is 100°C-320°C. It will be appreciated that the sintering temperature includes but is not limited to 100°C, 150°C, 200°C, 250°C, 300°C or 320°C.

[0046] Furthermore, the sintering time is 1 h-40 h. It can be understood that the sintering time includes but is not limited to 1 h, 5 h, 10 h, 20 h, 30 h, 40 h, preferably 5 h-30 h.

[0047] Optionally, the sintering process is performed in a nitrogen atmosphere and / or an inert atmosphere, wherein the inert atmosphere is selected from an argon atmosphere and / or a helium atmosphere.

[0048] It is understood that the halide of Li refers to a compound containing only Li and X elements, and the halide of M refers to a compound containing only M and X elements.

[0049] S2, the Li a MX b The material and GaF3 are subjected to ball milling reaction under anhydrous conditions, so that the Li a MX b The surface of the material forms a shell layer to obtain a halide solid electrolyte, wherein the Li a MX b The mass ratio of the material to the GaF3 is 1:0.003-1:0.02, the ball milling speed is 500rpm-800rpm, and the ball milling time is 1min-10min.

[0050] Specifically, under anhydrous conditions, Li a MX b The material and GaF3 come into contact and react in situ under the action of ball milling. a MXb LiX is the main component in the material, and the reactivity of Li is greater than that of the M element, which makes the atomic migration rate of LiX greater and easier to react with GaF3 to form nLiX-GaF3. For example, when X is Cl, LiCl and GaF3 react to form nLiCl-GaF3. That is, in Li a MX b A shell layer is formed on the surface of the material, and by controlling the speed and time of ball milling, the Li a MX b The components on the surface of the material react with GaF3 only for a short time, so that the shell formed is basically composed of nLiX-GaF3, which is conducive to making the shell have good softness. In addition, by controlling the Li a MX b The mass ratio of the material and GaF3 can make Li a MX b The surface of the material is evenly covered with a shell layer while ensuring the conductivity of lithium ions.

[0051] In step S2, the ball milling medium is selected from at least one of zirconium oxide and silicon nitride, preferably zirconium oxide.

[0052] Furthermore, the ball-to-material ratio is 10:1-50:1; it is understandable that the ball-to-material ratio may include but is not limited to 10:1, 20:1, 30:1, 40:1, 50:1.

[0053] In one embodiment, the Li a MX b The material and GaF3 are subjected to ball milling reaction.

[0054] Optionally, the Li a MX b The material and the GaF3 are subjected to ball milling reaction under vacuum or dry inert atmosphere. It is understood that vacuum or dry inert atmosphere is used to achieve anhydrous conditions so that Li a MX b A full in-situ reaction takes place between the material and GaF3 to avoid the occurrence of other side reactions.

[0055] Specifically, the Li a MX b When the material and the GaF3 are subjected to ball milling reaction in a dry inert atmosphere, the inert atmosphere is selected from a nitrogen atmosphere and / or an inert gas atmosphere, wherein the inert gas atmosphere is selected from an argon atmosphere and / or a helium atmosphere.

[0056] It is understood that in the preparation method of the halide solid electrolyte of the present invention, the ball milling method is used, and the ball milling conditions and Lia MX b The mass ratio of the material and GaF3 makes GaF3 and Li a MX b The Li halide on the surface of the material reacts in situ to generate nLiX-GaF3, which is uniformly coated on the Li a MX b The shell layer on the surface of the material is basically only nLiX-GaF3, and the reaction conditions are relatively mild and the operation method is simple.

[0057] Therefore, the preparation method of the halide solid electrolyte of the present invention has simple operation method, low cost, easy mass preparation and is suitable for industrial production.

[0058] In addition, the present invention also provides a secondary battery, wherein the secondary battery comprises the halide solid electrolyte as described above. The secondary battery has both excellent cycle performance and rate performance, and can enhance the commercial application value of the secondary battery.

[0059] And, a vehicle, comprising the secondary battery as described above.

[0060] Hereinafter, the halide solid electrolyte, its preparation method and application will be further described by the following specific examples. However, those skilled in the art will understand that the following examples are only used to illustrate the present invention and should not be regarded as limiting the scope of the present invention. If the specific conditions are not specified in the examples, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0061] Example 1

[0062] Taking Li3InCl6 as a benchmark, LiCl and InCl3 are weighed in a molar ratio of 3:1, added into a sealed ball mill, and ball milled at 550 rpm for 20 hours using a planetary ball mill to obtain ball milled powder, which is then sintered in an argon atmosphere, wherein the sintering temperature is 260°C, the sintering time is 4 hours, the ball milling medium is selected from zirconia, and the ball-to-material ratio is 30:1, to obtain Li3InCl6 material.

[0063] The Li3InCl6 material and GaF3 obtained above are weighed in a mass ratio of 1:0.004, added into a ball mill and sealed, and ball milled for 5 minutes at 750 rpm using a planetary ball mill to form 3LiCl-GaF3, i.e., a shell layer, wherein the ball milling reaction process is carried out in a dry argon atmosphere, the ball milling medium is selected from zirconia, and the ball-to-material ratio is 30:1, to obtain a halide solid electrolyte.

[0064] The halide solid electrolyte in this embodiment is characterized by transmission electron microscopy. Figure 1 As shown, from Figure 1 It can be seen that the halide solid electrolyte has a core-shell structure, the median particle size is about 2.5 μm, and the thickness of the shell is about 19 nm. At the same time, the elemental analysis of the core and shell of the halide solid electrolyte using electron probe microanalysis shows that the material of the core of the halide solid electrolyte of this embodiment is Li3InCl6, and the material of the shell is 3LiCl-GaF3.

[0065] Example 2

[0066] Compared with Example 1, Example 2 differs only in that the mass ratio of Li3InCl6 material to GaF3 is 1:0.006, and the other conditions are the same, thereby obtaining a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 2.5 μm, the material of the shell is 3LiCl-GaF3, and the thickness of the shell is about 28 nm.

[0067] Example 3

[0068] Compared with Example 1, Example 3 differs only in that the mass ratio of Li3InCl6 material to GaF3 is 1:0.018, and the other conditions are the same, thereby obtaining a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 2.5 μm, the material of the shell is 3LiCl-GaF3, and the thickness of the shell is about 88 nm.

[0069] Example 4

[0070] Compared with Example 1, Example 4 differs only in that the mass ratio of Li3InCl6 material to GaF3 is 1:0.0036, and the other conditions are the same, thereby obtaining a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 2.5 μm, the material of the shell is 3LiCl-GaF3, and the thickness of the shell is about 15 nm.

[0071] Example 5

[0072] Compared with Example 1, Example 5 differs only in that, taking Li3ScCl6 as a benchmark, LiCl and ScCl3 are weighed in a molar ratio of 3:1, and the other conditions are the same, to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 3.1 μm, the material of the inner core is Li3ScCl6, the material of the shell is 3LiCl-GaF3, and the thickness of the shell is about 18 nm.

[0073] Example 6

[0074] The difference between Example 6 and Example 1 is that Li 2.5Y 0.5 Zr 0.5 Cl6 was used as the benchmark, LiCl, YCl3, and ZrCl3 were weighed in a molar ratio of 2.5:0.5:0.5, and the other conditions were the same to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte was about 2.9 μm, and the material of the core was Li 2.5 Y 0.5 Zr 0.5 Cl6, the shell material is 3LiCl-GaF3, and the shell thickness is about 20nm.

[0075] Example 7

[0076] The difference between Example 7 and Example 1 is that Li 2.75 Dy 0.5 Ho 0.25 Zr 0.25 Cl6 was used as the benchmark, LiCl, DyCl3, HoCl3, and ZrCl3 were weighed in a molar ratio of 2.75:0.5:0.25:0.25, and the other conditions were the same to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte was about 3.5 μm, and the material of the core was Li 2.75 Dy 0.5 Ho 0.25 Zr 0.25 Cl6, the shell material is 3LiCl-GaF3, and the shell thickness is about 22nm.

[0077] Example 8

[0078] The difference between Example 8 and Example 1 is that Li 2.75 Er 0.5 Yb 0.25 Zr 0.25 Cl6 was used as the benchmark, LiCl, ErCl3, YbCl3, and ZrCl3 were weighed in a molar ratio of 2.75:0.5:0.25:0.25, and the other conditions were the same to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte was about 2.2 μm, and the material of the core was Li 2.75 Er 0.5 Yb 0.25 Zr 0.25 Cl6, the shell material is 3LiCl-GaF3, and the shell thickness is about 22nm.

[0079] Example 9

[0080] Compared with Example 1, Example 9 differs only in that, taking Li2ZrCl6 as a benchmark, LiCl and ZrCl3 are weighed in a molar ratio of 2:1, and other conditions are the same, to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 3.5 μm, the material of the core is Li2ZrCl6, the material of the shell is 3LiCl-GaF3, and the thickness of the shell is about 25 nm.

[0081] Example 10

[0082] Compared with Example 1, Example 10 differs only in that, taking Li4ScCl7 as a reference, LiCl and ScCl3 are weighed in a molar ratio of 4:1, and the other conditions are the same, to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 3.4 μm, the material of the shell is 3LiCl-GaF3, the material of the core is Li4ScCl7, the material of the shell is 3LiCl-GaF3, and the thickness of the shell is about 32 nm.

[0083] Embodiment 11

[0084] The difference between Example 11 and Example 1 is that Li3In 0.5 Sc 0.5 Cl6 was used as the benchmark, LiCl, InCl3, and ScCl3 were weighed in a molar ratio of 3:0.5:0.5, and the other conditions were the same to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte was about 3.2 μm, and the material of the core was Li3In 0.5 Sc 0.5 Cl6, the shell material is 3LiCl-GaF3, and the shell thickness is about 22nm.

[0085] Example 12

[0086] The difference between Example 12 and Example 1 is that Li 3.2 In 0.7 Lu 0.3 Cl 6.2 As a benchmark, LiCl, InCl3, and LuCl3 were weighed in a molar ratio of 3.2:0.7:0.3, and the other conditions were the same to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte was about 2.9 μm, and the material of the core was Li 3.2 In 0.7 Lu 0.3 Cl 6.2 The material of the shell is 3LiCl-GaF3, and the thickness of the shell is about 26nm.

[0087] Embodiment 13

[0088] Compared with Example 1, the only difference in Example 13 is that, in the step of preparing Li3InCl6 material, the ball milling speed is 400 rpm, the ball milling time is 30 h, the sintering temperature is 120°C, and the sintering time is 30 h; in the step of forming the shell layer, the ball milling speed is 500 rpm, the ball milling time is 10 min, and the other conditions are the same, and a halide solid electrolyte is obtained, wherein the median particle size of the halide solid electrolyte is about 2.2 μm, and the thickness of the shell layer is about 16 nm.

[0089] Embodiment 14

[0090] Compared with Example 1, Example 14 differs only in that, in the step of preparing Li3InCl6 material, the ball milling speed is 800 rpm, the ball milling time is 8 h, the sintering temperature is 290°C, and the sintering time is 2 h; in the step of forming the shell layer, the ball milling speed is 600 rpm, the ball milling time is 8 min, and the other conditions are the same, thereby obtaining a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 2.8 μm, and the thickness of the shell layer is about 18 nm.

[0091] Comparative Example 1

[0092] The only difference between Comparative Example 1 and Example 1 is that it does not contain the step of preparing the shell layer, that is, the halide solid electrolyte Li3InCl6 is directly obtained.

[0093] Comparative Example 2

[0094] LiCl and GaF3 were weighed in a molar ratio of 2:1, added into a sealed ball mill, and ball milled for 12 h at 750 rpm using a planetary ball mill to obtain a 2LiCl-GaF3 solid electrolyte.

[0095] Comparative Example 3

[0096] LiCl and GaF3 were weighed in a molar ratio of 3:1, added into a sealed ball mill, and ball milled for 12 h at 750 rpm using a planetary ball mill to obtain a 3LiCl-GaF3 solid electrolyte.

[0097] Comparative Example 4

[0098] Compared with Example 1, Comparative Example 4 differs only in that, in the step of forming the shell layer, the ball milling time is 15 min, and the other conditions are the same, to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 2.5 μm, the material of the shell layer is 3LiCl-InCl3-GaF3, and the thickness of the shell layer is about 4 nm.

[0099] Comparative Example 5

[0100] Comparative Example 5 is different from Example 1 only in that, in the step of forming the shell layer, the ball milling speed is 400 rpm, the ball milling time is 15 min, and the other conditions are the same, to obtain a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 2.5 μm. In this comparative example, since suitable ball milling conditions are not adopted, there is almost no in-situ reaction between the Li3InCl6 material and GaF3, that is, there is only a simple physical mixture between the two, and therefore, the obtained halide solid electrolyte is basically a physical mixture of the Li3InCl6 material and GaF3.

[0101] Comparative Example 6

[0102] Compared with Example 1, Comparative Example 6 differs only in that the mass ratio of Li3InCl6 material to GaF3 is 1:0.04, and the other conditions are the same, thereby obtaining a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 2.5 μm, the material of the shell is 3LiCl-GaF3, and the thickness of the shell is about 205 nm.

[0103] Comparative Example 7

[0104] Compared with Example 1, Comparative Example 7 differs only in that the mass ratio of Li3InCl6 material to GaF3 is 1:0.002, and the other conditions are the same, thereby obtaining a halide solid electrolyte, wherein the median particle size of the halide solid electrolyte is about 2.5 μm, the material of the shell is 3LiCl-GaF3, and the thickness of the shell is about 10 nm.

[0105] Comparative Example 8

[0106] Li3InCl6 material was prepared according to the method of Example 1, 3LiCl-GaF3 electrolyte was prepared according to the method of Comparative Example 3, and then Li3InCl6 material and 3LiCl-GaF3 were directly mixed in a mass ratio of 1:1 to obtain a composite solid electrolyte.

[0107] The solid electrolytes prepared in Examples 1-14 and Comparative Examples 1-8 were subjected to ionic conductivity tests, electrochemical oxidation potential tests, and surface Young's modulus tests. The test results are shown in Table 1, wherein the specific test methods are as follows:

[0108] Ion conductivity test: Weigh 100 mg of electrolyte powder and place it inside the mold for pressurization. Apply 300 MPa of pressure to the electrolyte powder for pressurization. Under the pressure, use an electrochemical workstation (Solarton1260) and electrochemical impedance measurement to measure the impedance value of the electrolyte material at room temperature (25°C). The real value of the impedance at the measurement point where the absolute value of the phase of multiple impedances is the smallest is used as the resistance value RSE of the electrolyte material relative to ion transfer. Using this resistance value, based on the formula σ=(RSE×S / t) -1 , and the ionic conductivity is calculated. Wherein, σ is the ionic conductivity, RSE is the resistance value of the measured electrolyte material, S is the surface area of ​​the electrolyte material under pressure, and t is the thickness of the electrolyte material under pressure.

[0109] Electrochemical oxidation potential test: The electrochemical oxidation stability potential was measured using linear voltammetry. The cell configuration was BE / SSE+C / SSE / Li, the scan rate was 1 mV / s, and the voltage range was Voc~7V.

[0110] Young's modulus test: Place the sample on the sample stage of the atomic force microscope (AFM) and adjust the distance between the probe and the sample to ensure that the probe is in contact mode. Select the "force-displacement" mode on the AFM operation interface. Control the probe to press down into the sample surface at a loading rate of 400nm / s, record the interaction force and displacement between the probe and the sample, and obtain the relationship curve between force and displacement. Use the Hertzian contact theory to fit the force-displacement curve. By fitting the force-displacement curve, calculate the Young's modulus of the electrolyte material surface.

[0111] Table 1

[0112]

[0113] Solid-state batteries were prepared using the solid electrolytes prepared in Examples 1-14 and Comparative Examples 1-8. The specific preparation method was as follows: Under an argon atmosphere, the solid electrolytes and NCM811 positive electrode active materials prepared in the Examples and Comparative Examples were weighed in a mass ratio of 25:75, and they were evenly mixed to obtain a composite positive electrode material; 100 mg of Li6PS5Cl sulfide solid electrolyte was added to an insulating test sleeve with a diameter of 10 mm, a pressure of 300 MPa was applied and maintained for 2 minutes, and the solid electrolyte layer was formed; 20 mg of the obtained composite positive electrode material was poured into one side of the compressed electrolyte layer, a pressure of 360 MPa was applied and maintained for 5 minutes to form; a lithium indium alloy sheet was loaded into the other side of the electrolyte layer, and a pressure of 80 MPa was applied to form; finally, the composite positive electrode layer, the solid electrolyte layer, the lithium indium alloy sheet and the stainless steel collectors on both sides were combined to form an all-solid-state battery for testing.

[0114] Subsequently, the solid electrolytes prepared by Examples 1-14 and Comparative Examples 1-8 were used to prepare the corresponding all-solid-state battery packs for cycle performance tests. The test method is as follows: the assembled all-solid-state battery pack is placed in a 25°C constant temperature box. The test conditions are to use a current density of 0.1C and 2C to test the first week charge and discharge performance and cycle charge and discharge performance of the solid-state battery. The voltage range is set to 2.7-4.3V (Li + / Li), the test results are shown in Table 2.

[0115] Table 2

[0116]

[0117]

[0118] From the data in Table 1 and Table 2, it can be seen that the present invention uses the ball milling method and limits the ball milling conditions and Li a MX b The mass ratio of the material and GaF3 makes GaF3 and Li a MX b The Li halide on the surface of the material reacts in situ to generate nLiX-GaF3, thus forming a uniform coating on the Li a MX b The shell layer on the surface of the material, and the shell layer material is basically only nLiX-GaF3, so that the ionic conductivity of the halide solid electrolyte is above 0.8mS / cm, the electrochemical oxidation stability potential is above 4.2V, and the Young's modulus of the surface is below 12GPa, thereby effectively ensuring the overall chemical structure stability, high ionic conductivity and high electrochemical oxidation stability of the halide solid electrolyte. At the same time, the surface of the halide solid electrolyte has good softness, which can form a denser physical contact with the positive electrode active material and reduce the interface impedance, so that the positive electrode material has higher capacity and rate performance.

[0119] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0120] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A halide solid electrolyte, characterized in that: The halide solid electrolyte includes a core and a shell layer coated on the surface of the core. The chemical general formula of the core material is Li a MX b , and the chemical general formula of the main material of the shell layer is nLiX-GaF3, where 2 ≤ a ≤ 4, 4 < b ≤ 7, 1 ≤ n ≤ 5, M is selected from at least one of In, Zr, Hf or lanthanide elements, and X is selected from at least one of Cl, Br or I.

2. The halide solid electrolyte according to claim 1, characterized in that 2.5≤a≤3.5, 5≤b≤6.5, 1.5≤n≤4; And / or, M is selected from at least one of In, Zr, Hf, Y, Sc, Dy, Ho, Er or Yb; And / or, X is selected from Cl and / or Br.

3. The halide solid electrolyte according to claim 1, characterized in that The thickness of the shell layer is 1nm-50nm.

4. The halide solid electrolyte according to claim 1, characterized in that The median particle size of the halide solid electrolyte is 0.05 μm-100 μm.

5. A method for preparing a halide solid electrolyte according to any one of claims 1 to 4, characterized in that: The steps include: Provide Li a MX b materials, where 2 ≤ a ≤ 4, 4 < b ≤ 7, M is selected from at least one of In, Zr, Hf or lanthanide elements, and X is selected from at least one of Cl, Br or I; The Li a MX b The material and GaF3 are subjected to ball milling reaction under anhydrous conditions, so that the Li a MX b The surface of the material forms a shell layer to obtain a halide solid electrolyte, wherein the Li a MX b The mass ratio of the material to the GaF3 is 1:0.003-1:0.02, the ball milling speed is 500rpm-800rpm, and the ball milling time is 1min-10min.

6. The method for preparing a halide solid electrolyte according to claim 5, characterized in that: The Li a MX b In the step of ball milling the material and the GaF3 under anhydrous conditions, at least one of the following conditions is met: (1) The ball milling medium is selected from at least one of zirconium oxide and silicon nitride, and the ball-to-material ratio is 10:1-50:1; (2) Li a MX b The material and the GaF3 are subjected to ball milling reaction under vacuum or dry inert atmosphere.

7. The method for preparing a halide solid electrolyte according to claim 5, characterized in that: The Li a MX b material preparation method comprises the following steps: taking Li a MX b , where 2≤a≤4 and 4<b≤7, ball-milling a halide of Li and a halide of M, and then sintering to obtain the Li a MX b material.

8. The method for preparing a halide solid electrolyte according to claim 7, characterized in that: The Li a MX b In the method for preparing the material, at least one of the following conditions is met: (1) The ball milling speed is 400 rpm-800 rpm, and the ball milling time is 5 h-30 h; (2) The sintering process is carried out in a nitrogen atmosphere and / or an inert atmosphere, wherein the inert atmosphere is selected from an argon atmosphere and / or a helium atmosphere; (3) The sintering temperature is 100℃-320℃, and the sintering time is 1h-40h.

9. A secondary battery, characterized in that: The secondary battery comprises the halide solid electrolyte according to any one of claims 1 to 4.

10. A vehicle, characterized in that: The vehicle includes the secondary battery as claimed in claim 9.